OD POETYKI TYTUŁU DO STRUKTURY SENSU — O DWÓCH TYTUŁACH JEDNEGO OPOWIADANIA VLADIMIRA NABOKOVA - Ułanek, Małgorzata (Przegląd rusycystyczny, 2023)
The subject of the analysis in the article is V. Nabokov’s short story Catastrophe which in the proces of authorial translation into English received a new title — Details of a Sunset. Starting from the poetics of the title the following matters were considered: 1. creation of a hero in love — „half-god” Mark endowed with luminous attributes, connecting him with the mythical sphere (Eros, Amor), with the pre-beginning (Eden, the motif of childhood) 2. the category of the „sensitive narrator” — an involved observer of the events; 3. the oneiric sphere present in the short story refering to the myth, connected with the human drive towards higher values, with the eternal desire for happiness; 4. imagery and symbolics of the setting sun. It has been demonstrated that the mode of the sunset description and the alteration of the short story title allowed the author to accentuate axiological dimension of the literary work and thus set the relationship with the reader postulating a particular„elevation”to another level of understanding. Methodological inspirations for the present- ed considerations were taken from Roland Barthes’reflections, who by evaluating the word in the discourse points towards its sense-generating function.